Integrating Photovoice in Building Students’ Confidence in Facing Public Speaking Anxiety - Muhammad Yudhi Pranata (IAIN KENDARI, 2020)
The objective of this study is to determine to what extent the Photovoice method can build students’ confidence in facing public speaking anxiety. In this study, Photovoice was able to help students toward speaking in many aspects such as, enthusiasm improvement, eye contact and body language adeptness, critical thinking and also fluency. Speaking skill is essential in language learning and teaching process because the goal of learning as foreign language is able to communicate using the target language. However, most of EFL students tend to be more nervous if they speak English, and this will impact their other proficiencies. This case study involved approximately 2 students at second grade of language major of MAN 1 Kendari. To collect the data from the research, there were three kinds of instruments such as, rubric of public speaking to measure the level of students’ self-confidence, classroom observation and students’ reflection. The result can be seen through students’ marking scheme that showed both participants getting score 47 and 72 at the first performance, 71 and 80 at the second one, 100 and 100 at the last one and students’ reflection that indicate S1 and S2 have been influenced positively in terms of their self-confidence by using Photovoice. From classroom observation side, students’ improvements were seen by teaching activities and video recorder that was taken during research.